Grundrechte Klausur- und Examenswissen - Valentiner, Dana-Sophia; Petras, Maximilian; Hahn, Lisa; Wienfort, Nora (De Gruyter Studium, 2022)
This textbook examines the fundamental rights granted by the German constitution in an innovative way. A team from all over Germany has combined basic knowledge for students with more in-depth knowledge for state examination candidates, covering both European and international law as well. A number of examples and links to interactive exercises encourage critical thinking. Readers can comment on all texts on a digital platform.